Cancer Management - Hashad, Doaa (IntechOpen, 2012)
Cancer remains a major clinical challenge as a cause of death due to its frequent poor prognosis and limited treatment options in many cases. Cancer management book addresses various cancer management related topics including new approaches for early cancer detection and novel anti-cancer therapeutic strategies. This book is a collection of studies and reviews written by experts from different parts of the world to present the most up-to-date knowledge on cancer management.